(untitled) (Andamios, Revista de Investigación Social, 2014)
Our article aims to analyse the theoretical initiative of Chantal Mouffe giving a new meaning to ‘the political’ front of the consensual political rationality, supported by the liberal tradition. Such a perspective must face the challenge of a democratic reforms established by and for the pluralism of political identities. For this purpose, is brought to scene the binomial friend/enemy of Carl Schmitt to consider its transformation into another binomial: us/them in the context of the transformation of the antagonism into agonism. Will be considered its consequences in contrast with a scenario marked by increasing moralization of the political speeches. Moralization that does nothing but hide the lack of deep political debates in front of popular democratic demands.